ORAL HYPERPIGMENTATION IN END-STAGE CKD PATIENTS UNDERGOING HEMODIALYSIS: A CASE REPORT - Djati, Fanni Kusuma; Minullah, Nanda Asta; Octivany, Sherly; Febriharsari, Niken; Aditiawarman, Aditiawarman; Nugroho, Yunanto Dwi (Mandala Of Health, 2025)
Chronic kidney disease (CKD) is a progressive disease characterized by gradual and irreversible loss of kidney function over several months or years. According to Riskesdas 2018, the incidence of CKD in Indonesia is 0.38% (713,783 people) with 19.33% (2,850 people) undergoing hemodialysis therapy. Many CKD patients have related oral lesions, but attention to oral healthcare remains insufficient, especially in developing countries with higher rates of CKD patients. Several oral manifestations of CKD described in the literature include mucosal inflammation, mucosal petechiae, ecchymosis, skin and mucosal hyperpigmentation, fissured tongue, and coated tongue. A 51-year-old male with CKD was hospitalized in Mawar ward, Prof. Dr. Margono Soekarjo Regional Public Hospital. The patient presented of brown patches on his lips and oral cavity. Intraoral examination revealed lesions presenting as irregularly shaped macules with smooth brown margins on the lips and buccal mucosa. The patient was diagnosed with oral hyperpigmentation. Another case involved a 48-year-old female with stage 5 CKD who routinely underwent hemodialysis, presenting with brown patches on the lips, indented lesions on the lateral and dorsal tongue, and yellowish coloration on the dorsal tongue, diagnosed as fissured tongue and coated tongue. The manifestations that appear may be influenced by the kidney disease itself, consumed medications, or the therapy provided. Oral hyperpigmentation, coated tongue, and fissured tongue are some of the oral manifestations commonly found in end-stage CKD patients undergoing hemodialysis, with therapy aimed at improving patients' quality of life.